A method for preparing a shape memory composite material with self-heating function

By combining liquid metal with carbon fiber cloth to form a heating resistance, the problem of shape memory composite materials being affected by external forces during the recovery process in the prior art is solved, self-heating shape memory recovery is achieved, and the rigidity and aggregation of traditional fillers are avoided. Problem, improving shape recovery rate and speed.

CN116971183BActive Publication Date: 2025-02-07HARBIN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310950016.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-07
Estimated Expiration
2043-07-31

AI Technical Summary

Technical Problem

The existing shape memory composite materials are pulled by external forces from the heating film during the shape recovery process, which affects the recovery speed and shape recovery rate. In addition, traditional fillers have rigidity and aggregation problems in quantity and distribution, which affects the shape memory recovery effect.

Method used

The liquid metal is combined with carbon fiber cloth to form a heating resistance to realize the self-heating shape memory recovery of composite materials. By mixing liquid metal with volatile alcohol in an inert atmosphere or vacuum environment and sonicating it, an alcohol-liquid metal suspension is formed, evenly added or coated on a carbon cloth, the electrode is drawn out and the shape memory resin matrix is ​​coated. Material, curing treatment results in a shape memory composite material with a self-heating function.

Benefits of technology

Self-heating shape memory recovery is realized, which saves the customization and installation of heating films, saves costs, and the fluidity of liquid metal does not affect shape memory recovery, and the resistance value can be adjusted to meet different shapes and heating needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116971183B_ABST
    Figure CN116971183B_ABST
Patent Text Reader

Abstract

A method for preparing a shape memory composite material with a self-heating function belongs to the technical field of shape memory composite material preparation, and the specific scheme includes the following steps: step 1, in an inert atmosphere, liquid metal is mixed with an alcohol with a molecular weight less than 200 and ultrasonically treated to obtain an alcohol-liquid metal suspension; step 2, the alcohol-liquid metal suspension is uniformly dripped or coated on a carbon cloth, and the alcohol volatilizes to obtain a carbon cloth-liquid metal; step 3, electrodes are drawn out on the carbon cloth-liquid metal, and a shape memory resin matrix material is coated on the carbon cloth-liquid metal, and a shape memory composite material with a self-heating function is obtained by curing. The present invention attaches liquid metal to a reinforcing carbon fiber, and the liquid metal presents a flowable liquid state at room temperature and when the shape memory polymer is heated and restored, so there is almost no resistance or influence on the recovery effect of shape memory.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparation of shape memory composite materials, and in particular relates to a method for preparing a composite material capable of realizing self-heating shape memory recovery by customizing the resistance size. Background Art

[0002] Shape memory composite materials can achieve the characteristics of deformation and recovery at a specific temperature, and the shape can be designed in advance. They are widely used in aerospace, biomedicine, sensor braking, soft robotics and other fields. When their own temperature reaches above the glass transition temperature, they can achieve shape memory recovery, which belongs to thermal responsive composite materials. There are generally many ways to achieve shape memory recovery. One is to use an electric heating film for temperature recovery, and closely attach the heating film to the part that needs deformation recovery. However, due to the presence of the heating film, it will be pulled by the external force of the heating film when the shape is recovered, affecting the recovery speed and shape recovery rate. One method is to add conductive or magnetic particles to the matrix to achieve resistive heating or magnetocaloric effect to drive shape memory recovery. Most of them are done by adding carbon materials (carbon nanotubes), conductive micro / nano fillers, graphene, metal nanowires or magnetic particles such as ferroferric oxide to the polymer, which enter the polymer matrix to form a conductive / thermal network or use the magnetocaloric effect in an external magnetic field environment to make the composite material reach Tg. However, most of these fillers have a certain rigidity and tend to aggregate in the polymer matrix. If there are too few fillers, the heat generation effect is poor, the heating rate is slow, and the shape memory recovery time is long. If there are too many fillers, the modulus of the polymer will increase rapidly, which will have a greater impact on the ability to recover shape.

[0003] Liquid metal refers to metal that is liquid at room temperature. It is an amorphous, flowable liquid metal. Low melting point metals include gallium, indium, and their alloys. By adjusting the content of different components in the alloy, the melting point of the liquid metal can be controlled. Summary of the invention

[0004] In order to solve the problems existing in the background technology, the present invention provides a method for preparing a shape memory composite material with self-heating function, which utilizes the conductive property of liquid metal to form a heating resistor together with carbon fiber cloth, thereby achieving the effect of self-heating shape memory recovery of the composite material.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a shape memory composite material with a self-heating function comprises the following steps:

[0007] Step 1: In an inert atmosphere or a vacuum environment, the liquid metal is mixed with a volatile alcohol and subjected to ultrasonic treatment to obtain an alcohol-liquid metal suspension; preferably, the volatile alcohol is an alcohol with a molecular weight of less than 200.

[0008] Step 2: uniformly drip or apply the alcohol-liquid metal suspension on the carbon cloth, and the alcohol volatilizes to obtain the carbon cloth-liquid metal; the resistance value of the carbon cloth after dripping or applying the liquid metal will decrease, and the amount of resistance decrease can be controlled by controlling the quality of the liquid metal. Preferably, the coating method includes spraying, scraping or brushing.

[0009] Step 3: Lead out electrodes on the carbon cloth-liquid metal, and coat the carbon cloth-liquid metal with a shape memory resin matrix material, and perform a curing treatment to obtain a shape memory composite material with a self-heating function.

[0010] Furthermore, the liquid metal includes a combination of one or more of component A, component B and component C, wherein component A includes a combination of one or two of gallium and indium; component B includes a combination of one or more of gallium-zinc alloy and gallium-aluminum alloy; component C includes a combination of one or more of liquid metal alloys composed of two or more metal elements of gallium, indium, tin, bismuth and silver.

[0011] Furthermore, the C component includes a combination of one or more of gallium-bismuth alloy, gallium-tin alloy, and gallium-indium alloy.

[0012] Furthermore, in step one, the liquid metal is cleaned in a mixed acid before use, wherein the mixed acid comprises an organic acid solution and an inorganic acid solution, the volume ratio of the inorganic acid solution to the organic acid solution is 2-10:1, the mass fraction of the organic acid solution is 80%-100%, and the mass fraction of the inorganic acid solution is 1%-35%.

[0013] Furthermore, the organic acid includes a combination of one or more of formic acid, acetic acid, acrylic acid, and citric acid, and the inorganic acid solution includes a combination of one or more of sulfuric acid solution, hydrochloric acid solution, and nitric acid solution, and the concentrations of the sulfuric acid solution, hydrochloric acid solution, and nitric acid solution are all 0.1-5 mol / L.

[0014] Furthermore, in step one, the volatile alcohol includes a combination of one or more of methanol, ethanol, propanol, butanol, 2-methyl-1-propanol, ethanethiol, 1,3-propanedithiol, ethanedithiol, and 1-propanethiol.

[0015] Furthermore, in step 2, the mass of the liquid metal in the carbon cloth-liquid metal is 0.2-10 times the mass of the carbon cloth.

[0016] Furthermore, in step three, the shape memory resin matrix material includes one or more combinations of shape memory epoxy resin, shape memory polyurethane, shape memory polystyrene, and shape memory polyimide.

[0017] Furthermore, in step three, liquid metal is dripped at the junction of the electrode and the carbon cloth-liquid metal, and the liquid metal is solidified by cooling, so that the electrode and the carbon cloth-liquid metal are fixedly connected.

[0018] Furthermore, the electrode includes one of a copper sheet, a copper wire conductor, and an aluminum core conductor.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The present invention integrates shape memory and self-heating effects, which can save the customization and installation of heating films and save costs. It has great advantages, especially when facing irregular and complex shapes. The shape can be restored directly by electric heating, which is difficult to be completely covered by traditional heating films.

[0021] (2) Unlike the traditional method of adding conductive fillers to the resin matrix, the fillers in the resin matrix will increase the modulus of the resin and affect the shape memory recovery rate and shape memory recovery rate. The present invention attaches liquid metal to the reinforcing carbon fiber. The liquid metal presents a flowable liquid state at room temperature and when the shape memory polymer is heated and recovered, so it has almost no resistance or influence on the shape memory recovery effect.

[0022] (3) Liquid metal has good conductivity. Liquid metal and carbon fiber form a large number of connection paths, which can effectively reduce the resistance of carbon fiber cloth. The amount of resistance reduction can be adjusted according to the liquid metal content, so as to obtain the same heating power at a lower voltage or require a smaller working voltage at a predetermined heating power, thereby realizing electric heating recovery.

[0023] (4) Liquid metal has better thermal conductivity than general fillers. The heat generated by the carbon fiber and liquid metal through electric current can be better conducted to the resin matrix, realizing the ability of self-heating shape recovery without the help of external heat source after power is turned on. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a comparison diagram of alcohol and liquid metal before and after ultrasonic dispersion in Example 2;

[0025] Figure 2 It is a schematic diagram of the liquid metal distribution on the carbon cloth;

[0026] Figure 3 It is the change of resistance value of carbon fiber cloth before and after applying liquid metal Ga in nitrogen environment;

[0027] Figure 4 This is a block-shaped sample of a shape memory composite material with a self-heating function prepared in Example 2, wherein both ends are copper electrode sheets;

[0028] Figure 5This is a sample of a strip-shaped shape memory composite material with a self-heating function cut out in Example 2, wherein both ends are copper electrode sheets;

[0029] Figure 6 This is a temperature distribution diagram when a shape memory composite material sample with self-heating function is electrically heated. DETAILED DESCRIPTION

[0030] The technical solution of the present invention will be clearly and completely described below in conjunction with the drawings and embodiments. Obviously, the described embodiments are only part of the embodiments of the invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0031] Example 1

[0032] A method for preparing a shape memory composite material with self-heating function, the experimental process is as follows:

[0033] (1) Cut the carbon fiber cloth into the required size, such as (1.5-20) cm*(8-20) cm. The size of the cut release paper should be slightly larger than the size of the carbon cloth. Then place the carbon fiber cloth between two layers of release paper.

[0034] (2) The liquid metal includes a combination of one or more of component A, component B and component C, wherein the component A includes a combination of one or two of gallium and indium, the component B includes a combination of one or more of gallium-zinc alloy and gallium-aluminum alloy, and the component C includes a combination of one or more of low melting point alloys made of two or more metal elements of gallium, indium, tin, bismuth and silver. Preferably, the component C includes a combination of one or more of gallium-bismuth alloy, gallium-tin alloy and gallium-indium alloy. The liquid metal or liquid metal alloy is heated and melted in advance, one or more inorganic acid solutions of 0.1-5 mol / L sulfuric acid solution, hydrochloric acid solution or nitric acid solution are prepared, a small amount of one or more organic acids of formic acid, acetic acid, acrylic acid and citric acid are taken, and the inorganic acid solution and the organic acid solution are mixed in a volume ratio of 2-10:1, wherein the mass fraction of the inorganic acid solution is 1%-35%, and the mass fraction of the organic acid solution is 80%-100%. 10-30 ml of the mixed acid solution is placed in a beaker for later use.

[0035] (3) Take 0.5-5g of liquid metal and put it into the above mixed acid solution, shake and stir for 2-10 minutes, and the surface of the liquid metal will show a bright metallic luster.

[0036] (4) Take 10-30 ml of one or more small molecule alcohols selected from methanol, ethanol, propanol, butanol, 2-methyl-1-propanol, or one or more small molecule thiols selected from ethanethiol, 1,3-propanedithiol, ethanedithiol, and 1-propanethiol and pour them into a sealable vial, and place the sealable vial and the beaker containing the liquid metal and the mixed acid solution in the previous step in a vacuum glove box or an inert gas glove box. Use a syringe or a pipette to transfer the liquid metal in the mixed acid solution to the above-mentioned sealable vial, tighten the bottle cap, and wrap the bottle cap with a sealing strip or sealing tape. The liquid metal after acid treatment removes the oxide film and impurities, and is transferred to alcohol. After ultrasonic treatment, the liquid metal can be dispersed into small droplets. Since the -OH and -SH bonds of the alcohol can interact with the liquid metal, the dispersed liquid metal is prevented from aggregating again.

[0037] (5) Take out the vial containing the alcohol-liquid metal from the glove box, put it in an ultrasonic disperser, set the temperature to 30-200° C., and perform ultrasonic treatment for 3-30 minutes to obtain an alcohol-liquid metal suspension.

[0038] (6) A shape memory resin matrix material is prepared, wherein the shape memory resin matrix material includes one or more of shape memory epoxy resin, shape memory polyurethane, shape memory polystyrene, and shape memory polyimide. The alcohol-liquid metal suspension, carbon cloth, and shape memory resin matrix material after ultrasound are placed in a glove box. The alcohol-liquid metal suspension is evenly dripped on the carbon cloth, or sprayed on the carbon cloth using a spray pot or a sprayer. The effect of adjusting the resistance can be achieved by changing the amount of alcohol-liquid metal suspension dripped or sprayed, such as Figure 3 After applying liquid metal Ga, the resistance value of carbon fiber cloth decreases. Raising the temperature makes the alcohol volatilize, leaving the liquid metal, and obtaining carbon cloth-liquid metal. The mass of liquid metal is 0.2-10 times the mass of carbon cloth. Since liquid metal can interact with alcohol hydroxyl or thiol, the residual alcohol can prevent liquid metal from agglomerating and maintain a dispersed state. Alcohol can also react with resin to form part of the shape memory resin matrix material.

[0039] (7) Cut the conductive copper sheet into thin strips, 2-5 mm wide, and the length can be determined as needed, and used as electrodes. Other wires with good conductivity, such as copper wire or aluminum core wire, can also be used. After the alcohol is evaporated, the liquid metal connects the conductive copper sheet and the carbon cloth together. (Drop the liquid metal at the appropriate positions on both sides of the carbon cloth-liquid metal, place the electrode wire on the liquid metal, cool it down to solidify the liquid metal, and the electrode wire can be fixed to the carbon cloth-liquid metal.) Pour the prepared shape memory resin matrix material on the carbon cloth-liquid metal, cover it with release paper, evenly apply the shape memory resin matrix material, and flatten it with a glass plate, take it out of the glove box for curing, and obtain a shape memory composite material with self-heating function. The resin mass fraction of the composite material is in the range of 30%-70%.

[0040] (8) The prepared composite material was cut into strips with a width of 1.5-3 cm, and then subjected to a shape memory test, the shape fixation rate was recorded, and the shape recovery was tested when the composite material was heated by itself through power supply.

[0041] (9) The prepared composite material is made into the desired irregular and complex shape by bending, splicing, etc.

[0042] Example 2

[0043] A method for preparing a shape memory composite material with self-heating function, the experimental process is as follows:

[0044] (1) Cut a carbon fiber cloth of about 5 cm*8 cm, cut two pieces of 10*15 cm release paper, and then place the carbon fiber cloth between the two layers of release paper.

[0045] (2) Take 20 ml of 0.1 mol / L sulfuric acid solution and 3 ml of acrylic acid to obtain a mixed acid, which is then placed in a beaker for later use.

[0046] (3) 4 g of liquid metal gallium was placed in the above mixed acid solution, shaken and stirred for 2 min, and the surface of the liquid metal showed a bright metallic luster.

[0047] (4) Pour 15 ml of ethanol into a sealable vial, and place the sealable vial and the beaker containing the liquid metal and the mixed acid solution in the previous step in a vacuum glove box or an inert gas glove box. Use a syringe or a pipette to transfer the liquid metal gallium in the mixed acid solution into the above-mentioned sealable vial, tighten the bottle cap, and wrap the bottle cap with a sealing strip or sealing tape.

[0048] (5) Take out the vial containing alcohol and liquid metal from the glove box, put it in an ultrasonic disperser, set the temperature to 60°C, and perform ultrasonic treatment for 5 minutes to obtain an alcohol-liquid metal suspension, such as Figure 1 shown.

[0049] (6) Prepare a shape memory epoxy resin matrix material, put the alcohol-liquid metal suspension, carbon cloth, and shape memory epoxy resin matrix material into a glove box after ultrasonic treatment, drip the alcohol-liquid metal suspension evenly on the carbon cloth, increase the temperature to volatilize the alcohol, and obtain a carbon cloth-liquid metal. The schematic diagram is shown in FIG. Figure 2 As shown. The mass of liquid metal is about 0.5 times the mass of carbon cloth. Since liquid metal can interact with alcohol hydroxyl or thiol, the residual alcohol can prevent liquid metal from agglomerating and maintain a dispersed state. Alcohol can also react with resin to form a part of the shape memory resin matrix material.

[0050] (7) Take a 5 mm wide conductive copper sheet and a length of about 2.5 cm, which is used as an electrode. Liquid metal is dripped at appropriate positions on both sides of the carbon cloth-liquid metal, and a conductive copper sheet is placed on the liquid metal. The liquid metal is cooled to solidify, and the electrode conductive copper sheet can be fixed to the carbon cloth-liquid metal. Pour the prepared shape memory epoxy resin matrix material on the carbon cloth-liquid metal, cover it with release paper, evenly apply the shape memory epoxy resin matrix material, and flatten it with a glass plate. Take it out of the glove box for curing to obtain a shape memory composite material with self-heating function, such as Figure 4 As shown, the resin mass fraction of the composite material is about 55%.

[0051] (8) Cut the prepared composite material into strips with a width of 2 cm, such as Figure 5 Then the shape memory test was carried out to record the shape fixation rate, and the shape recovery was tested under the condition of self-heating by power supply, as shown in Figure 6 shown.

[0052] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a shape memory composite material with self-heating function, characterized in that: The following steps are involved: Step 1: In an inert atmosphere or a vacuum environment, a liquid metal is mixed with a volatile alcohol and subjected to ultrasonic treatment to obtain an alcohol-liquid metal suspension; Step 2: evenly drip or coat the alcohol-liquid metal suspension on the carbon cloth, and evaporate the alcohol to obtain the carbon cloth-liquid metal; Step 3: Lead out electrodes on the carbon cloth-liquid metal, and coat the carbon cloth-liquid metal with a shape memory resin matrix material, and perform a curing treatment to obtain a shape memory composite material with a self-heating function.

2. The method for preparing a shape memory composite material with self-heating function according to claim 1, characterized in that: The liquid metal includes a combination of one or more of components A, B and C, wherein the component A includes a combination of one or two of gallium and indium; the component B includes a combination of one or more of gallium-zinc alloy and gallium-aluminum alloy; the component C includes a combination of one or more of liquid metal alloys composed of two or more metal elements of gallium, indium, tin, bismuth and silver.

3. The method for preparing a shape memory composite material with self-heating function according to claim 2, characterized in that: The C component includes a combination of one or more of a gallium-bismuth alloy, a gallium-tin alloy, and a gallium-indium alloy.

4. The method for preparing a shape memory composite material with self-heating function according to claim 1, characterized in that: In step one, the liquid metal is cleaned in a mixed acid before use, wherein the mixed acid comprises an organic acid solution and an inorganic acid solution, wherein the volume ratio of the inorganic acid solution to the organic acid solution is 2-10:1, the mass fraction of the organic acid solution is 80%-100%, and the mass fraction of the inorganic acid solution is 1%-35%.

5. The method for preparing a shape memory composite material with self-heating function according to claim 4, characterized in that: The organic acid includes a combination of one or more of formic acid, acetic acid, acrylic acid, and citric acid, and the inorganic acid includes a combination of one or more of sulfuric acid, hydrochloric acid, and nitric acid.

6. The method for preparing a shape memory composite material with self-heating function according to claim 1, characterized in that: In step 1, the volatile alcohol includes one or more combinations of methanol, ethanol, propanol, butanol, 2-methyl-1-propanol, ethanethiol, 1,3-propanedithiol, ethanedithiol, and 1-propanethiol.

7. The method for preparing a shape memory composite material with self-heating function according to claim 1, characterized in that: In step 2, the mass of the liquid metal in the carbon cloth-liquid metal is 0.2-10 times the mass of the carbon cloth.

8. The method for preparing a shape memory composite material with self-heating function according to claim 1, characterized in that: In step three, the shape memory resin matrix material includes one or more of shape memory epoxy resin, shape memory polyurethane, shape memory polystyrene, and shape memory polyimide.

9. The method for preparing a shape memory composite material with self-heating function according to claim 1, characterized in that: In step three, liquid metal is dripped at the junction of the electrode and the carbon cloth-liquid metal, and the liquid metal is solidified by cooling, so that the electrode and the carbon cloth-liquid metal are fixedly connected; the electrode includes one of a copper sheet, a copper wire conductor, and an aluminum core conductor.

10. The method for preparing a shape memory composite material with self-heating function according to claim 1, characterized in that: In step 2, the resistance value of the carbon cloth will decrease after the liquid metal is dripped or coated, and the amount of resistance reduction can be controlled by controlling the quality of the liquid metal.

Citation Information

Patent Citations

  • Functionalized single layer graphite and polyurethane photo-induced shape memory composite material and preparation thereof

    CN101372553A

  • Preparation method of thermogenic shape memory polymer

    CN108219370A